COMPARISON OF GLOMERULAR FILTRATION RATE AND CHRONIC KIDNEY DISEASE PREVALENCE USING COCKCROFT-GAULT(C-G) AND MODIFICATION OF DIET IN RENAL DISEASE (MDRD FOR CHINESE FORMULA AMONG BALINESE POPULATION - Widiana, I Gde Raka; Suwitra, Ketut (Medicina, 2014)
Some community based study to determine the prevalence of chronic kidney disease has been conducted.It is reported that a reasonable rate of prevalence of CKD if calculated with different formula (either C-Gor MDRD). This study is aiming to compare estimated GFR and CKD prevalence determined byeitherC-G or MDRD and the new Chinese modified MDRD formulaThis study analyzed 4528 subjects from 7 areas in Bali Islands including 219(4.8%) subjects inSembiran, 302 (6.7%), Denpasar 302 (6.7%), Nusa Ceningan 305 (6.7%), Legian282 (6.2%) Blahbatuh3038(67.1%), Tenganan, 81(1.8%), and in Ubud 301(6.6%), consisted 2217 (49%) males and 2311(51%) females. It is found that there were a substantial differences and stepwise increase (79, 83, 86,and105 mL/min/ 1.73 m2), consecutively of mean of estimated-GFR if calculated by C-G, MDRD,MDRD for Chinese (if non-Chinese), and MDRD for Chinese (if Chinese) formula. It was also foundthat differences of prevalence rate CKD using different formulas. More than twenty percent (20.6%) ofCKD defined by estimated-GFR of 59 to 30 ml/min per 1.73m2 when were calculated by C-G, and 6.9and 6.8 percent if were calculated by MDRD and MDRD for Chinese (if non-Chinese), consecutively,however, it is much lower (2.2%) using MDRD formula for Chinese (if Chinese).In conclusion, this study shows difference inmeanvalues of e GFR and prevalence of CKD if calculatedusing different formulas. A valid formula is needed for specific Indonesian people. [MEDICINA2014;45:151-155].